227k views
2 votes
Help soon as possible

Help soon as possible-example-1
User MrPk
by
5.3k points

1 Answer

2 votes

Answer:

(3, - 1)

Explanation:

Given the 2 equations

2x - 3y = 9 → (1)

3x + 5y = 4 → (2)

Multiplying (1) by 5 and (2) by 3 will eliminate the term in y

10x - 15y = 45 → (3)

9x + 15y = 12 → (4)

Add (3) and (4) term by term

(10x + 9x) + (- 15y + 15y) = (45 + 12)

19x = 57 ( divide both sides by 19 )

x = 3

Substitute x = 3 into (1) or (2) to find corresponding value of y

(2) → 9 + 5y = 4 ( subtract 9 from both sides )

5y = - 5 ( divide both sides by 5 )

y = - 1

Solution is (3, - 1)

User Jitesh Upadhyay
by
5.1k points